PENGARUH SUHU AIR DAN LAMA PERENDAMAN TERHADAP PERKECAMBAHAN BIBIT SENGON BUTO (Enterolobium cyclocarpum) - Nur Keti; Yusanto Nugroho; Sulaiman Bakri (Jurnal Sylva Scienteae, 2022)
Planting sengon plants requires high-quality seeds that have high germination and vigor. Sengon seeds have a period of dormancy caused by hard seed coats. Breaking dormancy of sengon seeds needs to be done by soaking in hot water as a pretreatment so that the seed coat is softer and more permeable. The purpose of this study was to analyze the effect of water temperature and immersion time on growth potential, germination capacity, and vigor index of sengon buto seeds and the effectiveness of water temperature and immersion time on growth of sengon buto seeds. Treatment A3 with 24-hour immersion (B2A3) is the best combination for the three parameters with each value of 80% growth potential, 88.33% germination, and 71.67% vigor index. The results showed that water temperature and soaking time had an effect on the germination response of sengon buto seeds. The most effective water temperature for sengon buto seeds in this study was 100˚C with a soaking time of 24 hoursPenanaman tanaman sengon memerlukan benih yang bermutu tinggi dan memilikii daya berkecambah dan vigor yang tinggi. benih sengon memiliki masa dormansi yang diakibatkan oleh kulit benih keras. Pematahan dormansi benih sengon perlu dilakukan dengan perendaman menggunakan air panas sebagai perlakuan pendahuluan sehingga kulit benih lebih lunak dan permeable. Tujuan dari penelitian ini untuk menganalisis pengaruh suhu air dan lama perendaman terhadap Potensi Tumbuh, Daya Berkecambah, dan Indeks Vigor benih sengon buto dan efektifitas suhu air dan lama perendaman terhadap pertumbuhan benih sengon buto. Perlakuan A3 dengan perendaman 24 jam (B2A3) merupakan kombinasi terbaik untuk ketiga parameter dengan masing-masing nilai potensi tumbuh 80%, daya perkecambahan 88.33%, dan indeks vigor 71.67%. Hasil penelitian menunjukkan bahwa suhu air dan lama perendaman memiliki pengaruh terhadap respon perkecambahan biji sengon buto. Suhu air paling efektif untuk benih sengon buto pada penelitian ini ialah 100˚C dengan lama perendaman 24 jam